PENERAPAN PLATFORM LEARN SOCIAL DALAM KETERAMPILAN BAHASA INGGRIS MAHASISWA - Megawati Megawati; Eka Rista Harimurti (STKIP Pembangunan Indonesia Makassar, 2020)
Developing revolution industry 4.0 encourage human to be able for implementationinformation technology in which use internet. This give effect to the students’STKIP KusumaNegara English Education Program first semester. They have to mastery in using technology inorder that they can follow development. Also students can learn with Platform Learn Social.Platform learn social is a media or tools that use for transferring material in learning. Platformlearn social is kind of media in which can access by handphone or laptop. It can access by studentsif they have already account platform learn social. Advantages platform learn social is availablekind of levels so students can know their capability in learning English skills. Disadvantagesplatform learn social, there is no relation with the syllabus.Keywords : Learn social platform, Learning English